RuvC uses dynamic probing of the Holliday junction to achieve sequence specificity and efficient resolution - Karolina Maria Górecka (Nature Portfolio, 2019)
Holliday junctions (HJs) are four-way DNA structures that occur in DNA repair by homologous recombination which are removed by nucleases such as RuvC. Here the authors provide structural and biochemical details on the steps required for the completion of the process.